Internal Concentration Polarization in the Polyamide Active Layer of Thin-Film Composite Membranes - Zhou, Zongyao; Wang, Qun; Qin, Yiwen; Hu, Yunxia (Environmental science & technology, 2023)
A free-standing polyamide (PA) film is fabricated via in situ release from a thin-film composite (TFC) membrane achieved through the removal of the polysulfone support. The structure parameter S of the PA film is measured to be 24.2 ± 12.6 μm, which is about 87-fold of its film thickness. A significant decline in water flux of the PA film from an ideal forward osmosis membrane is observed. We find that the decline is predominantly influenced by the internal concentration polarization (ICP) of the PA film based on our experimental measurements and theoretical calculations. We propose that the asymmetric hollow structures of the PA layer with dense crusts and cavities may be the underlying cause of the occurrence of the ICP. More importantly, the structure parameter of the PA film can be reduced and its ICP effect can be mitigated by tuning its structures with fewer and shorter cavities. Our results for the first time provide experimental evidence to prove that the PA layer of the TFC membrane has the ICP effect, which could potentially provide fundamental insights into the influence of structural properties of PA on the membrane separation performance.